THE VALIDITY OF A MARRIAGE COVENANT BY TELEPHONE: AN APPROACH OF MASLAHAH AL-MURSALAH AND LAW NO. 1 OF 1974 CONCERNING MARRIAGE - Zuhdi Hsb (JURNAL DARMA AGUNG, 2022)
Law No. 1 of 1974 is part of the Islamic law transformation included in Indonesia's legislation. The law accommodates various aspects in the scientific context of Islamic law (Fiqh) regarding Marriage. One of the substantial definitions of Marriage put forward by the fuqaha is that axiologically Marriage is a way that is legalized by sharia to convey the character of human lust, which is placed in a noble place and is worth worship. One thing that must be answered from time to time by contemporary Fiqh, in this case, is the problem of Marriage which will continue to develop and be dynamic in line with current technological developments such as Marriage via telephone. This Marriage raises societal issues regarding its validity in contemporary jurisprudence and law No. 1 of 1974 concerning Marriage. This research was conducted qualitatively and through a literature search. The results of this study are that maslahah mursalah is essential as a method of ijtihad to answer challenges and legal phenomena that are dynamic following technological developments. Marriage via the telephone can be carried out and is legally valid even though it is not in one assembly if it meets the requirements and does not conflict with maqashid assyariah.